Material removal analysis for compliant polishing tool using adaptive meshing technique and Archard wear model - Arunachalam, Adhithya Plato Sidharth (2020)
In this paper, a simulation technique to predict the material removal profile is developed for a disc-shaped compliant polishing tool which is commonly used in robotic polishing. The methodology is based on the Archard wear model implemented with adaptive meshing technique in the commercial finite element ABAQUS® software. Initially, the effect of tool compliance on the static contact pressure distribution is investigated experimentally using pressure films. Numerical 3D finite element model is developed for the same in order to predict the contact pressure distribution which in turn influences the material removal profile prediction. The material removal study is carried out with a robotic arm, and the polished surface is later scanned for the material removal profile. In order to predict the material removal profile, the finite element simulation in ABAQUS® is carried out using ‘dynamic-implicit’ followed by executing the umeshmotion FORTRAN subroutine in the ‘general-static’ where the nodes are displaced based on the wear model and using Arbitrary Lagrangian-Eulerian (ALE). The results are again imported in dynamic implicit and the simulation is restarted. The cycle continues till the experimental polishing time is reached. The experimental and simulation results of contact pressure are in good agreement with each other and bring out the effect of tool compliance on dynamic pressure which in turns affects the overall three-dimensional material removal profile.